Augmented Reality and Its Application 2022
DOI: 10.5772/intechopen.99337
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent VR-AR for Natural Disasters Management

Abstract: Considering the significance of improving natural disasters emergency management and recognizing that catastrophe scenes are almost impossible to reconstruct in real life, forcing persons to experience real hazards violates both law and morality, in this research is presented an engine for Virtual Reality/Augmented Reality (VR/AR) that works enhancing human capacities for prevention, response and recovery of natural phenomena effects. The selected novel techniques have very advantageous qualities to overcome t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…There is no intelligent agent present to dynamically change the scenarios every time the user plays it. There is an AI component present in [4], where the system tries to recreate the scenario of disasters. The system is doing so with the dataset of earthquakes that occurred, inputting that information into a CART algorithm to predict what the scenario would have looked like.…”
Section: A Virtual Reality (Vr)mentioning
confidence: 99%
See 1 more Smart Citation
“…There is no intelligent agent present to dynamically change the scenarios every time the user plays it. There is an AI component present in [4], where the system tries to recreate the scenario of disasters. The system is doing so with the dataset of earthquakes that occurred, inputting that information into a CART algorithm to predict what the scenario would have looked like.…”
Section: A Virtual Reality (Vr)mentioning
confidence: 99%
“…Virtual disaster training provides a cost-effective and safe way to conduct disaster evacuation preparedness training. There are many works in literature that use virtual reality technology for disaster preparedness training [1], [2], [3], [4], [5], [6]. With AR/VR and Metaverse being the latest, most popular and rapidly accelerating field today, it is a great time to switch to virtual methods of training with the fast technological advancement of the HMDs (Head Mounted Displays) by various companies, which would enable people to prepare for disasters in a much more cost-effective and safer manner.…”
Section: Introductionmentioning
confidence: 99%
“…Trainees may be placed into the virtual environment and learn how to rescue people or human infrastructures buried by the debris flow. Several studies revealed that VR is widely used for such purposes, in the fields of fire safety (Chittaro and Ranon 2009;Smith and Ericson 2009;Rüppel and Schatz 2011) and earthquakes (Gong et al 2015;Ivanova et al 2016;Feng et al 2020). In our case, road users, early warning planners, and rescue operators can be trained on how and when to act after perceiving the debris flow hazard.…”
Section: Training Module For the First Responders For Safety Rescue O...mentioning
confidence: 99%